448 Revision Rate and Long-Term Outcome After Minimally Invasive Surgical Treatment of Lumbar Adjacent Segment Disease: A Retrospective Review of 176 Adjacent Level Reoperations. (1st April 2022) - Zhao, David; Fayed, Islam; Coleman, Garrett; Onyiah, Amara; Bharil, Sarika; Liu, Jiaqi; Anaizi, Amjad N.; Voyadzis, Jean-Marc; Sandhu, Faheem A.
Abstract : INTRODUCTION: The concept of accelerated degeneration at the level adjacent to a fused spinal segment is a well-known and studied phenomenon. Most current surgical paradigms address this with extension of fusion. However, decompression with laminectomy and/or discectomy, particularly with MIS approaches, are viable options. METHODS: A single-center retrospective review of consecutive cases from 2013-2020 was performed. All patients who underwent lumbar surgery for ASD were included. The primary outcome was need for revision surgery following either a decompression, microdiscectomy, or instrumented fusion for lumbar ASD. Multivariable regression analysis (chi-square and ANOVA) was performed on demographic, operative, and follow-up data. RESULTS: We identified 176 patients who underwent surgery for lumbar ASD with mean follow-up of 9.3 years. 129 patients were treated with fusion, 37 with laminectomy, and 10 with microdiscectomy. In total, 41 patients required revision surgery following their ASD operation: 28 (21.7%) after fusion, 10 (27%) after laminectomy, and 3 (30%) after microdiscectomy (p = 0.697). Symptomatic disc herniation manifested sooner requiring reoperation -- on average 43.8 months (p = 0.006) after index procedure. CONCLUSION: There was no significant difference in revision rate among patients undergoing extension of fusion, laminectomy, or discectomy in the treatment of lumbar ASD. Focal adjacent stenosis or disc herniation can be durably treated with MIS laminectomy or discectomy, respectively. Accelerated disc degeneration after discectomy for lumbar ASD may require a subsequent fusion. Lumbar ASD associated with mobile spondylolisthesis should be treated by extension of fusion.